Supramolecular association studied by Fluorescence correlation spectroscopy - Novo, Mercedes; Al-Soufi, Wajih (Frontiers in Chemistry, 2022)
A comprehensive description of a supramolecular system involves a full understanding of its thermodynamic and dynamic properties, as well as detailed knowledge of its structure. Fluorescence Correlation Spectroscopy (FCS) constitutes a powerful technique to acquire this information. Fluorescence correlation curves show a characteristic diffusion term that is related to the binding equilibrium constant or other thermodynamic properties of the supramolecular system. The association and dissociation rate constants of the binding process can be determined in FCS when the relaxation time of the binding is faster than the observation time—a regime called fast-exchange dynamics - in opposition to the slow-exchange regime. In all cases, structural information can be inferred from the diffusional properties of the supramolecular complexes. A short overview of the use of FCS for the study of supramolecular systems is given with examples which belong to the fast and slow regime.